2020
DOI: 10.1097/sla.0000000000004257
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Inflammation and Proenzyme Activation Are Associated With Clinically Relevant Postoperative Pancreatic Fistulas After Pancreas Resection

Abstract: Objective: We investigated the activation of pancreatic proenzymes and signs of peripancreatic inflammation in patients with clinically relevant postoperative pancreatic fistulas (POPFs). Summary Background Data: An increase of systemic amylase concentration was associated with POPFs. This suggested parallels in the pathomechanisms between the development of POPFs and pancreatitis. Methods: Trypsinogen, proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The presence of an ischemic/inflammatory process of the pancreatic remnant was suggested as the etiology in several pathologic reports, particularly in series considering operative revisions for Grade C POPF 11,20,37 . These patients indeed represent the most severe and rare scenarios of PPAP (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of an ischemic/inflammatory process of the pancreatic remnant was suggested as the etiology in several pathologic reports, particularly in series considering operative revisions for Grade C POPF 11,20,37 . These patients indeed represent the most severe and rare scenarios of PPAP (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…9,19 These pathophysiological events may trigger a series of cascading events causing acinar cell disruption, intracellular activation of proteolytic enzymes, pancreatic parenchymal edema, and peripancreatic inflammation, leading to local and/or systemic effects. 20 PPAP may impair the healing of the pancreatic remnant and/or anastomosis with the subsequent development of a postoperative pancreatic fistula (POPF). 21 However, even in the absence of POPF, it may also lead to other abdominal and systemic complications, such as organ space infection/intra-abdominal abscess, 22 hemorrhage, the systemic inflammatory response syndrome (SIRS), and systemic sepsis.…”
mentioning
confidence: 99%
“…Previous work from our unit has shown that POPF risk is associated with the acinar content of remnant pancreata but not fat content 5 . Moreover, there is an increasing body of evidence supporting the link between postoperative pancreatitis and POPF 9,10 . As pancreatic digestive enzymes originate from the acinar cell, a higher density of acinar cells in the remnant pancreas likely leads to an increased risk of postoperative pancreatitis and POPF 5 .…”
Section: Discussionmentioning
confidence: 84%
“…5 Moreover, there is an increasing body of evidence supporting the link between postoperative pancreatitis and POPF. 9,10 As pancreatic digestive enzymes originate from the acinar cell, a higher density of acinar cells in the remnant pancreas likely leads to an increased risk of postoperative pancreatitis and POPF. 5 The multivariable model in this work therefore demonstrates that pancreatic consistency acts merely as an imperfect surrogate marker of the acinar content of the remnant pancreas, which is the key histological determinant of postoperative pancreatitis and POPF.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of pancreatic juice exudation on the surrounding tissues will cause inflammation and adhesion, which will affect the difficulty of operation. The phenomena of liquid residue and increased tissue density can be observed in imaging ( 30 , 31 ). All the image data defining these indicators have been saved for reference, if necessary.…”
Section: Methodsmentioning
confidence: 99%